Technical Efficiency of Soybeans Commodity - Setiawan, Avi Budi; Bowo, Prasetyo Ari (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
This research aims to find out the description of soybean farming in Grobogan Regency, the efficiency of technical, price, and economy on soybean systems. Grobogan Regency is a major soybean producer in Central Java and Indonesia. Â Based on the research result, it reveals that soybean farming in Grobogan has still not been efficient yet in technic, price, and economy. It means that farmers have not been able to optimize the inputs to obtain the maximum output. This inefficiency condition occurs because the farmers are considered to use the production factors excessively. Besides damaging the nature, the use of excessive production factors also leads to increasing production costs but without maximal results. Therefore, it requires a series of attempts to give knowledge to the farmers in order to reach efficient conditions by hoping that potential to maximized profitKeywords: Efficiency, Soybean, Grobogan